Development of management and public administration: trends, challenges, mechanisms - Shkilnyak, Mykhailo; Melnyk, Alla; Vasina, Alla; Zhelyuk, Tetyana; Dudkina, Olena (Herald of Economics, 2025)
Analytical note on the results of the VI All-Ukrainian Scientific and Practical Conference with International Participation "Current Problems of Management and Public Administration in the Face of Modern Challenges", Zbarazh, ZUNU, May 15, 2025